Honing Scientific Logic: Cognitive Intervention Strategies in Scientific Literacy and Numeration for Primary School Children - Nancy Susianna; Yosephine Debbie Damayanti; Anggie Siti Perdani; Rinda Angghita Putri; William Xaveriano Waresindo; Elvinda Juita Grace Zai; Bernadus Albertus Salaisek; Theresia Susanti Salolosit (Jurnal Penelitian Pendidikan IPA, 2025)
This community service activity was carried out at MIS Nyalindung, Cisarua, with the aim of improving the scientific literacy and numeracy skills of elementary school students through a literacy- and STEM-based approach. This activity involved 53 students from grades 3 to 6, who were divided into two phases based on grade level. The intervention was carried out through a combination of reading literary and information texts, as well as simple experiments on changes in the states of objects. Evaluation was carried out through pretests and posttests, which showed a significant increase in students' average scores in both phases, with normalized gains of 0.38 and 0.47, respectively. The results of the paired t-test showed a statistically significant increase. In addition to cognitive improvements, this activity also showed a positive impact on the affective aspect, where 85% of students felt more motivated to learn science, and 90% expressed satisfaction with the learning methods used. The questionnaire data showed that most students had visual (43%) and kinesthetic (39%) learning styles, which supports the effectiveness of the multimodal approach in learning. This activity also contributed 450 literacy- and STEM-themed reading books as a form of ongoing support for strengthening literacy culture in schools. The results of observations showed an increase in active participation, the ability to work together, and communication skills of students. The role of teachers as facilitators also contributed to creating a fun and productive learning environment. Overall, this activity demonstrates that the literacy- and STEM-based approach is effective when implemented at the elementary school level and has a positive impact on fostering active, contextual, and sustainable learning.